HRM system strength and employee well‐being: the role of internal process and open systems. (25th June 2021) - Heffernan, Margaret; Cafferkey, Kenneth; Harney, Brian; Townsend, Keith; Dundon, Tony
Abstract : This article draws on HRM system strength to further a process‐based understanding of how HRM can impact employee well‐being. The research contributes to new understanding using internal process climate as a mediator in the HR system strength and employee well‐being relationship. In order to capture external influences, we also explore moderation in the form of open systems climate, thereby adding an important boundary conditioning logic to the debate. Hypotheses were tested on a sample of 585 employees across nine organisations in Malaysia. Results show that the strength of the HRM system significantly affects employee perceptions of well‐being. The internal process climate positively mediates this relationship, highlighting the merits of both a formal structure and a commitment‐focused HR architecture. Findings also support the moderating role of an open systems climate on this mediating relationship. The research highlights new avenues to better understand the impact of HRM system strength on well‐being across contexts and outcomes.